2007
DOI: 10.1088/1126-6708/2007/12/049
|View full text |Cite
|
Sign up to set email alerts
|

Emergent gravity from noncommutative gauge theory

Abstract: We show that the matrix-model action for noncommutative U(n) gauge theory actually describes SU(n) gauge theory coupled to gravity. This is elaborated in the 4-dimensional case. The SU(n) gauge fields as well as additional scalar fields couple to an effective metric G ab , which is determined by a dynamical Poisson structure. The emergent gravity is intimately related to noncommutativity, encoding those degrees of freedom which are usually interpreted as U(1) gauge fields. This leads to a class of metrics whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
227
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(231 citation statements)
references
References 63 publications
(139 reference statements)
4
227
0
Order By: Relevance
“…It was observed that a massless scalar and vector fields coupled to NC U (1) gauge field, after the SW mapping, has the same structure as that of fields coupled with gravity [8]. This suggestion, that gravity can emerge from NC electromagnetism, has been further studied and extended in [9,10]. Hence it is natural to ask whether the 2-form field coupled to photons in NC space-time has such an emergent gravity coupling.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that a massless scalar and vector fields coupled to NC U (1) gauge field, after the SW mapping, has the same structure as that of fields coupled with gravity [8]. This suggestion, that gravity can emerge from NC electromagnetism, has been further studied and extended in [9,10]. Hence it is natural to ask whether the 2-form field coupled to photons in NC space-time has such an emergent gravity coupling.…”
Section: Introductionmentioning
confidence: 99%
“…The basic hypothesis of our approach is that space-time is realized as 3+1-dimensional NC "brane" solution of such a model. The effective geometry and gravity on such a brane was clarified recently [1][2][3]: the effective metric is not fundamental but depends on the embedding and the Poisson structure, reminiscent of the open string metric [7]. This leads to an emergent gravity closely related to NC gauge theory, as anticipated in [5,6].…”
mentioning
confidence: 99%
“…(2.11). 4 for massless particles, the geodesics ofG ab coincide with those of G ab . Masses should be generated spontaneously, which is not considered here.…”
Section: Quantization and Induced Gravitymentioning
confidence: 91%
“…Then the conventional kinetic term (2.13) boils down to (2.11). Therefore in the point-particle limit, the trajectory of a fermion with action (2.11) will follow properly the geodesics of the metric 4 G ab , albeit with a different rotation of the spin. Furthermore, the induced gravitational action obtained by integrating out the fermion in (2.11) indeed induces the expected Einstein-Hilbert term…”
Section: Matrix Models and Effective Geometrymentioning
confidence: 99%
See 1 more Smart Citation